Utveckling av testrigg inom effektcirkulation - Andersson, Samuel; Nilsson, Patrik (2011)
Luleå University of Technology has since a long time been engaged in tribology research at the Department of Engineering Science and Mathematics. The research in transmission losses opened for a thesis project for when a new test rig for power recirculation was needed. The thesis is performed in Tribolab at Luleå University of Technology and Vicura AB has contributed its expertise in transmission and several components for the rig. Its main purpose and goal is that by developing a test rig enabling the study of operating conditions in a gear mesh, measuring the losses in a gearbox and determine the tribological components that perform mainly. It should also be used to distinguish idle losses and losses that increase with torque.In the initial phase of the work was a literature review of what exists in the current situation in the area carried out. One of the most known test rigs for power recirculation is FZG. In addition to the FZG rig Lulea University of Technology had another test rig in this area before. By gathering information from these and numerous other rigs an idea was created of what will be required. After this part there was a visit to Vicura AB in Trollhättan, here were several existing transmission tests discussed and past experience was aired.After the identication of problem areas a number of requirements were set. The functions that were required and those that were more desirable were specied. The development of the rig started with generating numerous concepts and making a layout. For concept selection a rough screening was carried out based on the experience of literature and the four remaining concepts utilized a concept weighting matrix. With a solid team concept began the next phase \Construction and Design \ in development. This is mainly of CAD models, drawings and assembling. Parts to the test rig was made by an external company, Nova industri, and some minor details have been manufactured at the university.To verify how the test rig performs dierent tests were set up, including tests ...